2003
DOI: 10.1385/bter:94:2:149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of X-Ray Radiation on Lipid Peroxidation and Antioxidant Systems in Rabbits Treated with Antioxidant Compounds

Abstract: The aim of this study was to investigate the effects of supplemental antioxidant vitamins and minerals on lipid peroxidation and on the antioxidant systems in rabbits exposed to X-rays. The rabbits were divided into two experimental groups and one control group, each group containing seven rabbits. The first group (VG) received daily oral doses of vitamin E (460 mg/kg live weight) and vitamin C (100 mg/kg live weight). The second group (MG) was fed a mineral-enriched diet that contained 60 mg manganese chlorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 15 publications
2
15
0
2
Order By: Relevance
“…1). These results are consistent with earlier literature (4,5,37). Plasma MDA levels decreased in extract‐treated groups with increasing extract doses (25–50 mg kg −1 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…1). These results are consistent with earlier literature (4,5,37). Plasma MDA levels decreased in extract‐treated groups with increasing extract doses (25–50 mg kg −1 ).…”
Section: Discussionsupporting
confidence: 94%
“…Methanol extract of heat‐processed neoginseng attenuated lipid peroxidation in rats induced by ferric ion or ferric ion plus ascorbic acid (34), Vietnamese ginseng saponin has preventive effects on the psychological stress‐induced brain cell membrane damage (35) and bacoside A (triterpenoid saponin) administration improved the antioxidant status and maintained the levels of trace elements (36). A number of researchers have showed that irradiation increased the formation of MDA (4,5,33). According to the results of the present study, when rats were exposed to XR (5–10 Gy) of whole‐body irradiation, lipid peroxidation was found to be significantly increased in the blood with XR dose (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Sirmali et al [25] reported that serum zinc and copper levels in a rat hind limb model were increased by VCE supplementation. Deger et al [26] reported that blood antioxidant levels such as glutathione, vitamins C and E in rabbit were not affected by radiation and multimineral (manganese, zinc, and copper) supplementation, although their values were increased by VCE supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Major biomarkers of oxidative damage to living cells are lipid peroxidation (LPx) products, DNA-hydroxylation and protein hydroxylation products (2). Efficient defense and repair mechanisms exist in living cells to protect against oxidant species (3). The antioxidative defense system is composed of methods to: transfer sensitive material to compartments better protected from the action of reactive species, complex transition metals, a potential source of electrons, thereby rendering them unreactive, inhibit vulnerable processes such as DNA replication, repair damaged molecules, initiate apoptosis, and, possibly most important considering the liability to internal and external modifying factors, activate antioxidant enzymes, and finally use a variety of direct free radical scavengers (4).…”
mentioning
confidence: 99%